STRATEGY FORMULATION FOR HOSPITALS IN REMOTE AREAS: CASE STUDY OF X HOSPITAL, WEST BORNEO PROVINCE, INDONESIA, 2019 - Dewi Citra Puspita; Adang Bachtiar (Yayasan Aliansi Cendekiawan Indonesia Thailand (Indonesian Scholars' Alliance), 2019)
Background: Located in remote area, X Hospital is facing various challenges as a private non-profit class C hospital. Therefore, it needs to develop an appropriate strategic plan for the year 2020-2024 to overcome challenges and achieve its vision. This study is aimed at identifying the strengths, weaknesses, opportunities and threats from internal and external strategic factors, determine strategic positioning, and formulate alternative strategies for X Hospital. Method: This is a preliminary study with qualitative - exploratory design. Data were collected through in-depth interviews, group discussions and observation. The interviews were conducted with 7 key informants holding strategic management positions. This study was conducted in two in-depth stages using Consensus Decision Making Group (CDMG) method to avoid bias. Data were analyzed using Internal Factor Evaluation (IFE) and External Factor Evaluation (EFE) matrixes at the input stage and Internal External (IE) and Threat Opportunity Weakness Strength (TOWS) matrixes at the matching stage. This study was conducted at X Hospital, West Borneo Province, Indonesia, from March to April 2019. Results: The IFE final score was 2.38 with strength (1.68) greater than weakness (0.70) and EFE score of 2.16 with threats (1.10) greater than opportunities (1.06). Such input stage results indicate that X Hospital has average response in utilizing its internal and external strategic factors where strengths are more prominent than weaknesses but the threats are still overshadowing its opportunities. Consequently, the results of matching stage place X Hospital on the position of hold or maintain strategies and formulate 11 alternative strategies that focus on market or product development. Conclusions: X Hospital is currently on a strategic position to develop its services as the basis for the five-year strategic planning. A new policy should be made to encourage the establishment of a network with private hospitals to promote healthcare in remote areas. Keywords: strategic plan, remote area, hospital, IE matrix, TOWS matrix